SUSTAINABILITY OF WOMEN'S MSMES: FINANCIAL LITERACY, FINANCIAL INCLUSION, AND FINTECH - Bunyamin Bunyamin; Andi Hadidu; Nurhani Nurhani; Nurfaedah Nurfaedah (Management Studies and Business Journal (PRODUCTIVITY), 2026)
This study aims to examine the influence of financial literacy and financial technology (Fintech) on financial inclusion and its implications for the sustainability of MSMEs managed by women. The research population included women MSME entrepreneurs in South Sulawesi Province, with a sample of 100 respondents selected using purposive sampling based on two criteria, namely (1) women MSME entrepreneurs and (2) type of business. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) approach. The results of the study indicate that financial literacy and financial inclusion have a positive effect on the sustainability of women's MSMEs. Conversely, fintech does not have a significant effect on business sustainability. In addition, financial literacy has been proven to affect financial inclusion. The novelty of this study is that it integrates the variables of financial literacy and fintech in the context of the sustainability of women's MSMEs with various business type variables and uses the SEM-PLS method, which is considered the most appropriate for analyzing the causal relationship between variables. The implications of the research results emphasize the importance of improving financial literacy through comprehensive education and training programs and an inclusive approach to broaden understanding of fintech use, strengthening managerial capacity and financial management skills. Adequate knowledge-based capacity is a key factor in supporting resilience and the sustainability of women's MSMEs in the future.